2019
DOI: 10.1007/s15010-019-01275-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of voriconazole and amphotericin B against Candida albicans, Candida krusei, and Cryptococcus neoformans in human cerebrospinal fluid

Abstract: Purpose Fungal central nervous system (CNS) infections show a high mortality rate and only a few antifungal agents are available to treat these infections. We hypothesize that the different biochemical properties of human cerebrospinal fluid (CSF) compared to the standard growth medium lead to the altered activity of antifungal agents in CSF. We investigated the in vitro activity of two of these agents, i.e., amphotericin B (AmB) and voriconazole (VOR), against three different fungi in CSF in comparison to sab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The MIC is defined as the lowest concentration inhibiting the microorganism’s growth [ 7 ]. The results show that AMB exhibited an MIC of 0.25 µg/mL ( Figure S2B ), which is consistent with published studies [ 42 , 43 ]. In comparison, the PCL-AMB NPs exhibited a MIC of 0.06 µg/mL ( Figure S2A ), which is significantly lower than that of the free drug.…”
Section: Resultssupporting
confidence: 92%
“…The MIC is defined as the lowest concentration inhibiting the microorganism’s growth [ 7 ]. The results show that AMB exhibited an MIC of 0.25 µg/mL ( Figure S2B ), which is consistent with published studies [ 42 , 43 ]. In comparison, the PCL-AMB NPs exhibited a MIC of 0.06 µg/mL ( Figure S2A ), which is significantly lower than that of the free drug.…”
Section: Resultssupporting
confidence: 92%
“…The efficacy of antifungal agents is known to be influenced by media composition (Klepser et al 1997 ; Muller et al 2001 ). In one recent in vitro study, drug activity against central nervous system fungal pathogens, activity in sabouraud-dextrose broth differed markedly compared to cerebeospinal fluid media (al Jalali et al 2019 ). In another investigation, it was noted that growth, adhesion and biofilm formation of Candida species was profoundly affected by choice of media culture (Weerasekera et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were exposed to two concentrations of AmB (0.5 μ g/mL or 4 μ g/mL) for 48 hours at 35°C and the viability ratio and CFU/mL were determined using the cell counting method and plate count method, respectively. These concentrations were chosen in accordance to clinical concentrations reported in the literature [ 50 , 51 ]. The cytotoxicity of blank MCPs at the corresponding concentration used for 0.5 μ g/mL and 4 μ g/mL was also evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of the cell suspension was determined using a hemocytometer and 5 × 10 3 cells were added to tubes containing different concentrations of AmB (0.5 μ g/mL or 4 μ g/mL). The concentrations of AmB used for this study were chosen in accordance with clinical concentrations reported in the literature [ 50 , 51 ]. The sterile test tubes were incubated for 48 hours at 35°C and 250 rpm.…”
Section: Methodsmentioning
confidence: 99%